IMPROVING STUDENT’S SPEAKING SKILL THROUGH TALKING CHIPS STRATEGY: A PILOT STUDY - Maria Kartini (JURNAL ILMU BUDAYA, 2021)
In English, there are five essential speaking's aspects that need to be mastered by English learners such as content, fluency, coherence, grammar, and pronunciation. Unfortunately, it is difficult to be reached by EFL students. Due to this, the English teachers are required to find appropriate teaching strategies to help EFL students improve their speaking skills. The aims of this study were 1) to develop the implementation of the talking chips strategy in teaching speaking skills, 2) to improve student’s speaking skills through the talking chips strategy. The results showed that there was an improvement in students’ speaking skills after implementing the talking chips strategy. It was proven by the significant different scores of students’ speaking skills between cycle 1 and cycle 2.